4th international UNIVEST: Strategies towards collaborative learning - Univest 13 (OmniaScience, 2014)
With that main goal, the IV International UNIVEST Conference was proposed as a forum to debate and exchange ideas about university teaching and learning processes and the importance of placing students in the centre of these processes.